COMMUNITY KNOWLEDGE OF ARJOSARI VILLAGE, KALIPARE DISTRICT, MALANG DISTRICT, EAST JAVA ABOUT SAVING OF RAINWATER - Rahmah Dara Lufira; Lilik Zuhriyah; Satwika Desantina Muktiningsih; Aldila Putri Rahayu; Ken Diah Mangar Nastiti (Universitas Ahmad Dahlan, 2021)
Arjosari Village, Kalipare Subdistrict, Malang Regency, experiences drought every year; this makes the villagers buy water when the dry season comes. This research aims to find out how much knowledge of the people of Arjosari Village, Kalipare District, Malang Regency in saving rainwater used as an alternative to fulfil water needs in the dry season. The research method used was a descriptive survey method with a sample of 82 people. Survey studies are